The Influence of Biomechanics on Sports Kinesiology Techniques: Impact on Performance and Injury Prevention - Andi Atssam Mappanyukki (Journal Physical Health Recreation (JPHR), 2025)
The biomechanical and kinesiology approach provides a scientific foundation for understanding the relationship between force, movement, and neuromuscular control in enhancing performance and preventing injuries. This study aims to analyze the influence of biomechanics on sports kinesiology techniques through a literature review of studies published between 2020 and 2025 sourced from PubMed, ScienceDirect, SpringerLink, BMC, BMJ, and The Lancet. The findings show that integrating both disciplines improves movement efficiency, postural stability, and physiological adaptation in athletes through the application of real-time biomechanical feedback and integrative neuromuscular training (INT). In addition, wearable sensor technology assists in detecting mechanical loads and individual injury risks. Thus, biomechanics serves not only as an analytical tool but also as a foundation for developing adaptive, safe, and sustainable training strategies to support optimal athletic performance.